Flexible Neural Representations of Value in the Primate Brain - DANIEL SALZMAN, C. (2007)
The amygdala and orbitofrontal cortex (OFC) are often thought of as components of a neural circuit that assigns affective significance—or value—to sensory stimuli so as to anticipate future events and adjust behavioral and physiological responses. Much recent work has been aimed at understanding the distinct contributions of the amygdala and OFC to these processes, but a detailed understanding of the physiological mechanisms underlying learning about value remains lacking. To gain insight into these processes, we have focused initially on characterizing the neural signals of the primate amygdala, and more recently of the primate OFC, during appetitive and aversive reinforcement learning procedures. We have employed a classical conditioning procedure whereby monkeys form associations between visual stimuli and rewards or aversive stimuli. After learning these initial associations, we reverse the stimulus-reinforcement contingencies, and monkeys learn these new associations. We have discovered that separate populations of neurons in the amygdala represent the positive and negative value of conditioned visual stimuli. This representation of value updates rapidly upon image value reversal, as fast as monkeys learn, often within a single trial. We suggest that representations of value in the amygdala may change through multiple interrelated mechanisms: some that arise from fairly simple Hebbian processes, and others that may involve gated inputs from other brain areas, such as the OFC.